الإنتاج الصناعي في مملكة الانباط - al-Dalaeen, Marwan Atef (Journal of Al-Tamaddun, 2009)
The Nabataean realm is considered among Arab kingdoms that had advanced industries during the pre-Islamic time. Their products appeared in markets in the different parts of the Arabian Peninsula, and reached as far as Puteoli (modern Pozzuoli) in Italy, Rhodes Island in Greece. Nabataean industries varied, as the Nabataean territories were rich in different minerals such as gold, silver, iron and copper. The Nabataean industrial prosperity can be attributed to the availability of raw material such as the asphalt, copper iron and other natural resources. Furthermore crops, including palm, olive and balm were known in the area. All these factors contributed to the Nabataean kingdom be advanced in the industrial sector in comparison to neighboring areas.